Heteroligand cobalt(II) complexes with some aromatic acid hydrazides and L-histidine - N.V. Troshanin; T.I. Bychkova (Учёные записки Казанского университета: Серия Естественные науки)
Bіomplex formation in the ternary systems cobalt(II) – benzoic / p-methoxybenzoic / o-hydroxybenzoic acid hydrazide – L-histidine has been studied by the methods of spectrophotometry and mathematical modelling in the aqueous solutions with 1.0 mol dm–3 KNO3 as a background. The formation constants and spectral parameters of homo- and heteroligand complexes have been determined. It has been shown that the stability of the complexes formed with o-hydroxybenzoic acid hydrazide was higher than that with p-methoxybenzoic and benzoic acid hydrazides. Extra stabilization of the heteroligand complexes has been identified and interpreted. The quantum-chemical optimization of the cobalt(II) heteroligand complex structure containing the single-charged anionic form of o-hydroxybenzoic acid hydrazide and histidine zwitterion has been carried out.